2013
DOI: 10.1001/jamaoto.2013.4491
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computed Tomography in the Prediction of Extracapsular Spread of Lymph Node Metastases in Squamous Cell Carcinoma of the Head and Neck

Abstract: Computed tomography cannot be used to reliably determine the presence of pathologic ECS. Radiologic findings suggestive of ECS should not be relied on for treatment planning in squamous cell carcinoma of the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 39 publications
(31 reference statements)
7
62
0
1
Order By: Relevance
“…In a second recent study, Chai et al 20 concluded that "radiologic findings suggestive of ECS should not be relied on for treatment planning in squamous cell carcinoma of the head and neck." Chai et al 20 used a 5-point scale for the evaluation of radiographically determined ECS, included a wider range of primary tumors, and had 2 different observers with specificities of 54% and 84%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a second recent study, Chai et al 20 concluded that "radiologic findings suggestive of ECS should not be relied on for treatment planning in squamous cell carcinoma of the head and neck." Chai et al 20 used a 5-point scale for the evaluation of radiographically determined ECS, included a wider range of primary tumors, and had 2 different observers with specificities of 54% and 84%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative imaging had a PPV for predicting ENE > 2 mm of only 44-55%, which is too low for treatment decision making. We and others [10,18] have found the present techniques inadequate for identifying ENE in patients with HPV-associated OPSCC.…”
Section: Discussionmentioning
confidence: 62%
“…We did not evaluate matted nodes, given previously demonstrated poor interobserver agreement for this parameter. 20 The negative predictive value of rECS on CT is poor; however, rECS on CT as evidenced by adjacent structure invasion has a good positive predictive value. [20][21][22][23] We found, in multivariate analysis, that rECS with invasion of surrounding soft tissues was an independent predictor of TF and that rECS correlated significantly with solid lymph node metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…20 The negative predictive value of rECS on CT is poor; however, rECS on CT as evidenced by adjacent structure invasion has a good positive predictive value. [20][21][22][23] We found, in multivariate analysis, that rECS with invasion of surrounding soft tissues was an independent predictor of TF and that rECS correlated significantly with solid lymph node metastasis. Recently Liu et al 24 did not find rECS to be an independent predictor of TF in a subset of patients with HPV-related OPSCC, though there was a trend toward worse survival in this group.…”
Section: Discussionmentioning
confidence: 95%